Actualizing Buya Hamka’s Holistic Educational Thought in Islamic Full-Day Schooling - Nabila Aisyi; Mahmudah Mahmudah; Murdan Murdan (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2026)
This study examines the actualization of Buya Hamka’s holistic educational thought in the implementation of an Islamic full-day school program at an Indonesian primary school. While previous studies have largely discussed full-day schooling as a strategy for character formation, limited attention has been given to how the educational ideas of Indonesian Muslim scholars are translated into contemporary school practices. Using a qualitative case study design, data were collected through interviews, observation, and documentation involving school leaders, teachers, Qur’anic instructors, and students. The data were analyzed thematically through data reduction, data display, and interpretive conclusion drawing, supported by source and technique triangulation. The findings reveal that Buya Hamka’s educational principles are actualized through four interconnected practices: curriculum integration between the national curriculum and Islamic enrichment curriculum, systematic religious habituation through prayer and Qur’anic literacy, teacher exemplarity in character formation, and the creation of joyful and supportive learning environments. These practices demonstrate that full-day schooling provides an institutional space for integrating intellectual, spiritual, moral, emotional, and social development. The study contributes to Islamic education scholarship by showing that Buya Hamka’s educational thought can function not only as a normative-philosophical concept but also as an analytical framework for understanding holistic education in modern Islamic primary schools. The findings imply that Islamic full-day schooling can become a strategic model for strengthening character education when supported by curriculum coherence, religious habituation, teacher role modelling, and a conducive school culture.